PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS VIII SMP NEGERI 7 PADANG - Agung Syukriardi (Jurnal Edukasi dan Penelitian Matematika, 2022)
The purpose of this research is to discribe whether applying the Student Teams Achievement Division type of cooperative learning model can improve students' understanding of mathematical concepts. This type of research is   a quantitative descriptive research using a pre-experimental design. The research design used is a one shot case study with the research subjects being class VIII students of SMP Negeri 7 Padang in 2021/2022. Data collection in this study consisted of five quizzes and a final test consisting of eight essay questions. The data analysis technique is analyzing the quiz scores at each meeting and analyzing the final test scores. The percentage of completeness of the quiz scores and the average quiz scores of students for the five meetings increased at each meeting. The average mathematical concept understanding test for all indicators is 84.15 with very good criteria. Keywords – Cooperative Learning, STAD, Understanding of Mathematical Concept